L’analyse des activités du patient : une occasion de réinterroger la notion de travail - Joris Thievenaz (Éducation et Socialisation)
This article questions the commonly accepted notion of work, based on an analyze of the activities of a patient during his recovery journey. The steps of analyzing work in relation to education and training leads to broadening the field of activities commonly studied to get to the day to day tasks of the subjects. A research conducted in immersion in a hospital department allowed us to identify actions that usually stay ‘’in the dark’’ because self-conducted. Based on the theories and methods of the interactionist sociology of the Chicago School, we will focus here on a case study.